RELEVANSI LAPORAN KEUANGAN PADA PERUSAHAAN-PERUSAHAAN MANUFAKTUR TERDAFTAR DI BURSA EFEK INDONESIA - Lestari, Ikhlazia Indah; Kamaludin, Kamaludin; Midiastuty, Pratana Puspa (JURNAL FAIRNESS, 2016)
This study aims to test whether there is a higher value relevance of financial ratios after the IFRS convergence than before the IFRS convergence and whether there is a difference in the value relevance of financial ratios in explaining stock prices between the periods before and after the IFRS convergence.The sample in this study was manufacturing companies listed on the Indonesia Stock Exchange in 2011-2012. Using the purposive sampling technique, 94 companies were the samples of this study. The results show that there is no value relevance of the value of the liquidity and solvency ratios after IFRS which is higher than before IFRS and there is a value relevance of the value of the profitability ratio after IFRS which is higher than before IFRS. The results also show that there is a difference in the effect of the relevance of financial ratios in explaining stock prices after the application of IFRS compared to before the application of IFRS.